A method for preparing a dielectric material for a friction nanogenerator

By using materials such as manganese carbonate powder and dilute hydrochloric acid in a friction nanogenerator, the problems of cumbersome preparation steps and high cost in the prior art are solved, and the preparation of dielectric materials with simple processes and low cost are achieved, and the degree of material consumption is easy to observe.

CN116410517BActive Publication Date: 2025-05-02HENAN UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310634600.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-05-02
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

The existing preparation methods for tribolic dielectric materials of friction nanogenerators are cumbersome, costly, and have a small practical range. They cannot be popularized on a large scale, and cannot effectively solve the problem of changing dielectric materials of friction nanogenerators.

Method used

By adding manganese carbonate powder and curing agent to PDMS, stirring evenly to obtain a slurry, applied to a film mold and dried, then immersed in dilute hydrochloric acid and dopamine hydrochloric acid solutions, and finally immersed in nano-silver wire solution, a dielectric material for friction nanogenerators was prepared.

Benefits of technology

The method is simple in process and low in cost. The prepared dielectric material has color and is easy to observe its consumption. It solves the problem of replacement of dielectric materials for friction nanogenerators and has good dielectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116410517B_ABST
    Figure CN116410517B_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a dielectric material for a friction nanogenerator in the technical field, comprising the following steps: step 1: adding manganese carbonate powder and a curing agent to PDMS, and stirring evenly to obtain a slurry for standby use; step 2: applying the slurry evenly to a film mold, and drying to obtain a composite film; step 3: soaking the composite film in a dilute hydrochloric acid solution to obtain a porous film, and then washing the porous film with water and drying it; step 4: soaking the porous film in a 0.2 mol / L to 0.5 mol / L dopamine hydrochloride solution for 48 to 72 hours to obtain a hydrophilic film, and then washing the hydrophilic film with water and drying it. The process for preparing a dielectric material for a friction nanogenerator according to the invention is simple, low in cost, easy to operate, and the prepared film is colored, and its consumption degree can be intuitively observed when used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field, and in particular to a method for preparing a dielectric material for a friction nanogenerator. Background Art

[0002] As modern electronic products develop towards low power consumption, collecting usable or wasted energy from the surrounding environment and converting it into electrical energy has become a green development trend. Triboelectric nanogenerator is a new type of micro-nano energy technology that uses multiple forms of contact friction to cleanly and efficiently collect energy from the environment, thereby realizing the self-driving and sustainable operation of electronic devices. It is particularly worth mentioning that TENG has the advantages of low cost, simple preparation, high output power, multiple working modes, wide material selection, and high conversion efficiency. Therefore, it has very broad application prospects in energy collection and information sensing; therefore, the preparation and selection of triboelectric materials are particularly important.

[0003] Based on the vertical contact-separation mode friction nanogenerator, the contact material is now mostly selected as a composite material. For example, embedding nanoparticles in a polymer matrix can not only change the electrical properties of the material surface, but also change the dielectric properties of the material, thereby affecting the electrostatic induction process; however, this preparation method has complicated steps, is relatively expensive, has a small practical scope, cannot be popularized on a large scale, and cannot achieve the expected effect. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a dielectric material for a friction nanogenerator in order to solve the above problems.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] A method for preparing a dielectric material for a triboelectric nanogenerator comprises the following steps:

[0007] Step 1: Add manganese carbonate powder and curing agent to PDMS, and stir evenly to obtain slurry for later use;

[0008] Step 2: evenly apply the slurry to the film mold and dry it to obtain a composite film;

[0009] Step 3: Soak the composite film in a dilute hydrochloric acid solution for 12h~13h to obtain a porous film, and then wash the porous film with water and dry it;

[0010] Step 4: Soak the porous film in a 0.2 mol / L to 0.5 mol / L dopamine hydrochloride solution for 48 to 72 hours to obtain a hydrophilic film, and then wash the hydrophilic film with water and dry it.

[0011] Preferably, the dried hydrophilic film is immersed in a 1% to 2% nanosilver wire solution for 10 to 14 hours to improve the dielectric capacity of the hydrophilic film, and then washed with water and dried.

[0012] Preferably, the mass ratio of the PDMS to the manganese carbonate powder is 1:2.4-2.6.

[0013] Preferably, the mass ratio of the PDMS to the manganese carbonate powder is 1:2.5.

[0014] Preferably, the mass ratio of the PDMS to the curing agent is 10:1.

[0015] Preferably, the solvent of the nano silver wire solution is water.

[0016] Preferably, the concentration of the dilute hydrochloric acid solution is 15% to 20%.

[0017] Preferably, the slurry is evenly applied to a film mold, and dried at a temperature of -0.010 MPa to -0.020 MPa for 20 to 30 min to obtain a composite film.

[0018] Preferably, the water washing is rinsing.

[0019] The beneficial effects are:

[0020] 1. The method uses manganese carbonate as the material to prepare the dielectric material for the friction nanogenerator, which has simple process, low cost, easy operation, and the prepared film has color, which is not available at present;

[0021] 2. The degree of consumption of the dielectric material prepared by this method can be intuitively observed during use, so that the maintenance personnel can directly know whether the dielectric material of the friction nanogenerator needs to be replaced.

[0022] The additional technical features and advantages of the present invention will be more clearly explained in the following description, or can be understood through the specific practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 It is a schematic diagram of the film obtained by the present invention scanned by SEM electron microscope;

[0025] Figure 2 is a schematic diagram of the film obtained by the present invention using EDS energy spectrum analysis;

[0026] Figure 3It is the FTIR spectrum of the thin film obtained by the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the description of the present invention, it is necessary to understand that the terms indicating orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0030] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0031] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the inventive product is usually placed when in use. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0032] In addition, the terms "horizontal", "vertical", "overhanging" and the like do not mean that the components are required to be absolutely horizontal or overhanging, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0033] In the present invention, unless otherwise clearly specified and limited, a first feature being above or below a second feature may include the first and second features being in direct contact, or may include the first and second features not being in direct contact but being in contact through another feature between them. Moreover, a first feature being above, above, and above a second feature includes the first feature being directly above and obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being below, below, and below a second feature includes the first feature being directly below and obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0034] Embodiment 1: A method for preparing a dielectric material for a triboelectric nanogenerator, comprising the following steps:

[0035] Step 1: Add manganese carbonate powder and curing agent to PDMS, and stir evenly to obtain slurry for later use;

[0036] Furthermore, the mass ratio of the PDMS to the manganese carbonate powder is 1:2.4-2.6; the mass ratio of the PDMS to the curing agent is 10:1.

[0037] Step 2: evenly apply the slurry to the film mold and dry it to obtain a composite film;

[0038] Furthermore, the slurry is evenly applied to a film mold, and dried at a temperature of -0.010 MPa to -0.020 MPa for 20 to 30 min to obtain a composite film.

[0039] Step 3: Soak the composite film in a dilute hydrochloric acid solution for 12h-13h to obtain a porous film, and then wash the porous film with water and dry it;

[0040] Furthermore, the concentration of the dilute hydrochloric acid solution is 15% to 20%; further, the porous film obtained by the treatment with the dilute hydrochloric acid solution is rinsed with a large amount of clean water and then dried in a dryer.

[0041] In this way, hydrochloric acid and manganese carbonate are chemically reacted, and the film will slowly turn light yellow as the immersion time goes by. That is to say, the immersion ends after the film turns light yellow, so the immersion time is not specifically limited here.

[0042] Step 4: Soak the porous film in a 0.2 mol / L~0.5 mol / L dopamine hydrochloride solution for 48~72 hours, then wash the hydrophilic film with water and dry it;

[0043] Further, the porous film obtained by the treatment with the dopamine hydrochloride solution is rinsed with a large amount of clean water and then dried in a dryer;

[0044] This arrangement can change the porous film from hydrophobic to hydrophilic, and the film will gradually turn black as the immersion time goes by, that is, the immersion ends after the film turns black, so the immersion time is not specifically limited here.

[0045] Furthermore, in order to improve the dielectric capacity of the hydrophilic film, the dried hydrophilic film was immersed in a 1% nanosilver wire solution for 10-14 hours, then washed with water and dried;

[0046] Furthermore, the hydrophilic porous film obtained by the treatment with the nanosilver wire solution is washed with a large amount of clean water and then dried using a dryer;

[0047] In this way, the film will gradually turn into silver-black as the soaking time goes by, that is, the soaking is completed after the film turns into silver-black, so the soaking time is not specifically limited here.

[0048] In Example 1, step 1: adding manganese carbonate powder and a curing agent to PDMS, and stirring evenly to obtain a slurry for later use;

[0049] The mass ratio of PDMS to manganese carbonate powder is 1:2.4; the mass ratio of PDMS to curing agent is 10:1.

[0050] Step 2: Evenly spread the slurry on the film mold, and put the film mold into a vacuum drying oven with a vacuum degree of -0.010MP for 25 minutes and then take it out to obtain a composite film.

[0051] Step 3: Soak the composite film in a 20% dilute hydrochloric acid solution for 12 hours and then take it out to obtain a porous film. Then rinse the porous film with a large amount of clean water and then dry it with a dryer.

[0052] Step 4: Soak the dried porous film in a 0.5 mol / L dopamine hydrochloride solution for 60 hours and then take it out to obtain a hydrophilic film, then rinse it with a large amount of clean water, and then dry it in a dryer.

[0053] In Example 2, the hydrophilic film obtained in Example 1 is immersed in a 1% nanosilver wire solution for 12 hours, then taken out, rinsed with a large amount of clean water, and then dried in a dryer to obtain a hydrophilic, porous film with enhanced dielectric capacity, which can be used as a dielectric material in a friction nanogenerator.

[0054] In Example 3, step 1: adding manganese carbonate powder and a curing agent to PDMS, and stirring evenly to obtain a slurry for later use;

[0055] The mass ratio of PDMS to manganese carbonate powder is 1:2.5; the mass ratio of PDMS to curing agent is 10:1.

[0056] Step 2: Evenly spread the slurry on the film mold, and put the film mold into a vacuum drying oven with a vacuum degree of -0.002MP for 22 minutes and then take it out to obtain a composite film.

[0057] Step 3: Soak the composite film in a dilute hydrochloric acid solution with a concentration of 18% for 13 hours and then take it out to obtain a porous film. Then rinse the porous film with a large amount of clean water and then dry it with a dryer.

[0058] Step 4: Soak the dried porous film in a 0.4 mol / L dopamine hydrochloride solution for 65 hours and then take it out to obtain a hydrophilic film, then rinse it with a large amount of clean water and then dry it in a dryer.

[0059] Step 5: Soak the hydrophilic film in a 2% nanosilver wire solution for 10 hours, then take it out, rinse it with a large amount of clean water, and then dry it in a dryer to obtain a hydrophilic, porous film with enhanced dielectric capacity. This film can be used as a dielectric material in a friction nanogenerator.

[0060] In other examples, multiple hydrophilic, porous films with enhanced dielectric capacity are obtained by changing the mass ratio of PDMS to manganese carbonate powder, for example, the mass ratio of PDMS to manganese carbonate powder is 1:2.45, 1:2.55, 1:2.6, etc.

[0061] After tensile strength, elastic modulus, elongation at break, and compression tests including hardness, elasticity, recovery and cohesion, and comprehensive analysis of the test results, it was concluded that the best film quality was obtained when the mass ratio of PDMS to manganese carbonate powder was 1:2.5.

[0062] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a dielectric material for a triboelectric nanogenerator, characterized in that: The following steps are involved: Step 1: Add manganese carbonate powder and curing agent to PDMS, and stir evenly to obtain slurry for later use; Step 2: evenly apply the slurry to the film mold and dry it to obtain a composite film; Step 3: Soak the composite film in a dilute hydrochloric acid solution for 12h~13h to obtain a porous film, and then wash the porous film with water and dry it; Step 4: The porous film is immersed in a 0.2 mol / L to 0.5 mol / L dopamine hydrochloride solution for 48 to 72 hours to obtain a hydrophilic film, and then the hydrophilic film is washed with water and dried; Step 5: Soak the dried hydrophilic film in a 1% to 2% nanosilver wire solution for 10 to 14 hours to improve the dielectric capacity of the hydrophilic film, then wash with water and dry.

2. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 1, characterized in that: The mass ratio of the PDMS to the manganese carbonate powder is 1:2.4-2.

6.

3. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 2, characterized in that: The mass ratio of the PDMS to the manganese carbonate powder is 1:2.

5.

4. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 1, characterized in that: The mass ratio of the PDMS to the curing agent is 10:

1.

5. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 1, characterized in that: The solvent of the nano silver wire solution is water.

6. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid solution is 15% to 20%.

7. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 1, characterized in that: The slurry is evenly spread on a film mold, and dried at a temperature of -0.010 MPa to -0.020 MPa for 20 to 30 min to obtain a composite film.

8. The method for preparing a dielectric material for a triboelectric nanogenerator according to claim 1, characterized in that: The water washing is flushing.

Citation Information

Patent Citations

  • Flexible nanometer friction generator and preparation method thereof, and prepared sensor

    CN106601329A

  • Method for preparing porous polymer micro needle by using template method and application thereof

    CN109364366A

  • Flexible dry electrode and preparation method therefor

    WO2023045107A1